(3NUNUI GdeTQhYGJ GdYGeI (B:s (3efVhQ GbJUGOj (B/s - (3HQj, Rjf GdYGHOjf Hf YHO Gddgs ((3GdQjGV(B: s (3GdfTQ GdYdej hGdeWGHY(B, s, 2005)
(3GdCSGS GdfXQj dNUNUI GdeTQhYGJ GdYGeI(B-(3NUNUI bWGYj Gdfbd hGdEJUGdGJ;NUNUI GdefGaY GdYGeI(B:(3GdeGA hGdcgQHGA(B-(3NUNUI GdNOeGJ GdYGeI(B:(3GdJYdje hGdUMIs
Keywords: (3GdCSYGQs; (3GdEfJGLs; (3GdShbs; (3GdUMIs; (3GdeTQhYGJ GdYGeIs; (3NUNUI GdcgQHGAs